Â PENGARUH PENDIDIKAN KESEHATAN TERHADAP PERUBAHAN SIKAP IBU DALAM MENCEGAH TERSEDAK PADA ANAK DI POS PAUD KUNCUP CERIA DESA BAKUNG PRINGGODANI KEC. BALONG BENDO KAB. SIDOARJO - Yulianti, Indra; Hariyanto, Agus (JURNAL KEPERAWATAN SEHAT, 2016)
Choking is a very serious incident that threatens life. More than 50 children die each year from choking on foreign objects or food. The mothers showed a negative attitude towards the action in preventing choking which is about 60%. Provide health education on the prevention of choking in children is expected to change ones attitude. The purpose of this study was to prove whether there are differences in attitudes before and after health education with extension methods to change the attitude of mothers to prevent choking in children in the Pos Paud Kuncup Ceria. The method used is a pre-experimental design with one group pretest-posttest design. Population in research in was all mothers whose children attend early childhood Pos Paud Kuncup Ceria totaling 25 people. The sample in this study are all mothers whose children attend early childhood Pos Paud Kuncup Ceria. The sampling technique is a type of non-probability sampling total sampling as many as 25 respondents. Data taken using a quetionaire. Having collected the data analysis with frequency distribution. The result shows no difference in the attitude of the mother before and after health education to prevent choking in children with an average of 44.48 before health education be given 51.08 after health education . Based on the above results are expected to further improve the health personnel, guidance and counseling to improve the mothers attitude that the way to prevent choking in children can be overcome in accordance with what has been described and is able to perform these actions independently.Keywords: Health Education, Attitude, Choking